Metaverse as the Solution to the Absence of a Constitutional Court Moot Courtroom in Universities - Hidayah, Nur Putri; Wicaksono, Galih Wasis; Amiludin, Amiludin; Al Sakinata, Annisa'; Arcelia, Allysa Sonia; Andesti, Kiki; Muafika, Siti Nurmala Lailatul; Saleha, Meisya Maulidina (Universitas Negeri Semarang, 2024)
Courses related to procedural law are practicum courses with Course Learning Outcomes (CLO)/ Capaian Pembelajaran Mata Kuliah (CPMK) students who can simulate trials in court. In this case, the moot courtroom's urgency is to provide an infrastructure for students to conduct moot trials. One of the practicum courses is the Constitutional Court's Judicial Procedural Law. Students who take this course must be competent and able to practice in the objective realm of justice. However, based on the observation and tracing results, the service activities' partners do not have a moot courtroom in the constitutional court, so they cannot carry out moot court in the course. Digital/virtual space, known as Metaverse, is a solution for procuring infrastructure for the constitutional court's moot courtroom. The results of this service show that the Metaverse Moot Court of the Constitutional Court is an appropriate technology-based product that is the only quick solution to the absence and limitations of the Constitutional Court's moot courtroom at Partner universities. Partners do not need to spend millions to billions of Rupiahs to procure facilities and infrastructure for the Constitutional Court's moot courtroom. In addition, this product is a solution to time constraints, considering that the campus has operational hours while students are still required to be proficient in practicing proceedings at the Constitutional Court. Finally, the virtual reality technology product implemented in this pseudo-courtroom provides an immersive experience like the real atmosphere in the courtroom. It makes students more excited and increases motivation to practice the trial.